Customer churn in a telecomunications company - Zima, Marek; Vencovský, Filip; Zimmermann, Pavel, 1980-; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2023)
The main business case is to prevent customers from stopping using telecommunication services by going to the competition. So called customer churn is a variable we are trying to estimate in order to reach this goal. Such prediction is going to be estimated by using machine learning algorithms and data provided by specific telecommunication company. Due to the privacy protection and customer privacy all data available to the reader are going to be anonymized. Cooperation with telecommunications company management is a key to the successful implementation.
Vedoucí práce: Filip Vencovský
Závěrečná práce - Institut celoživotního vzdělávání (MBA)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet